Perceptions of Compulsory Secondary Education (ESO) Spanish Language and Literature Teachers towards Inclusive Language - ROMERA CIRIA, MAGDALENA; Lezaun Beortegui, Rosa María (Huarte de San Juan. Filología y Didáctica de la Lengua, 2025)
This study examines the perceptions and attitudes of Spanish Language and Literature teachers in Compulsory Secondary Education (ESO) towards inclusive language in the Autonomous Community of Navarre. Based on a mixed approach, data were collected from teachers at three educational institutions with varying levels of participation in a co-education programme. The results reveal a polarisation of views: while a small minority defends a traditionalist perspective that considers language neutral and rejects inclusive modifications, the majority of participants recognise the transformative potential of inclusive language to highlight inequalities and promote equity. The participation in co-education programmes is highlighted as a positive influence on attitudes towards these practices, although challenges remain in their daily implementation. The study further emphasises the need for training to overcome resistance and consolidate inclusive language as both an educational tool and a means of social change.
Keywords: inclusive language; sexist language; co-education; educational programmes; social change